'My Plate' Nutrition Education for Adolescents in the Context of Fulfilling Children's Nutrition to Prevent Stunting - Jelita Delima Khumairo , Ridha Millati, Muhammad Ananda Alfarizi, Muhammad Nur Ramadani, Mutiara Cah (Borneo Community Development, 2024)
Stunting is one of the nutritional problems in toddlers that has become a global concern in recent years, especially in low- and middle-income countries including Indonesia. Therefore, the program carried out in the form of efforts to reduce stunting by increasing adolescents' knowledge about the importance of fulfilling nutrition in the food eaten through Piringku education. The method of implementation is by giving a pre-test and then presenting the material and giving a post-test to measure understanding after receiving the material. The program took place on August 14, 2023 at SMP and SMK Muhammadiyah Desa Panggung.